Konsep Al-Raja’ dalam Al-Qur’an dan Hubungannya terhadap Mental - Husna, Rifqatul; Ni’mah, Nailun (Ushuluna: Jurnal Ilmu Ushuluddin, 2023)
Among the factors of increasing depression rates in Indonesia is motivated by a sense of hopelessness or loss of hope in someone. This is one of the reasons for raising the theme in this thematic study. Research that aims to reveal more deeply the meaning of al-raja' in the Qur'an so that it is expected to be applied in everyday life, and make the concept of al-raja' as a motivation in facing every phase of life that will be lived. This study uses thematic method of interpretation (mauḍū’i) by collecting verses about al-raja' in the Qur'an along with data related to the study of the meaning of al-raja'. There are 7 concepts of al-raja' in the Qur'an that are more applicable in contrast to previous studies that tend to be overshadowed by Sufism studies, namely: hope for Allah Swt., prayer, tawakkal, hope for forgiveness, hope for just retribution, hope for obedience, and hope for guidance. This concept is expected to be applied easily in every situation, so that it becomes a source of strength, peace, and comfort for individuals in facing life's challenges and tests.